Current scenario of viral diseases in Turkish poultry industry. Issue 4 (1st December 2019) - Bayraktar, E.; Umar, S.; Yilmaz, A.; Turan, N.; Yilmaz, H.
Abstract : The Turkish poultry industry has rapidly developed in the last decade. Viral pathogens continue to threaten the industry, causing economic losses worldwide, including Turkey. At present, infectious bronchitis and infectious laryngotracheitis are major challenges, as are, to a lesser extent, avian metapneumovirus, infectious bursal disease, Marek's disease and chicken infectious anaemia. The prevalence and severity of these diseases in Turkish chickens varies depending on environmental and management factors, vaccination strategies and biosecurity measures. In Turkey, infectious bronchitis virus, including vaccine and field strains, were detected in 83.6% (41/49) and 64.2% (9/14) vaccinated broiler and layer flocks, respectively. Virulent and vaccine strains of infectious bursal disease virus were found in 83.5% (1548/1855) of excised bursa Fabricius from vaccinated broilers. Virulent Marek's disease virus was found in 19.93% (120/620) of spleens from vaccinated chickens. Infectious laryngotracheitis virus in commercial poultry and Newcastle disease in backyard chickens have been detected. To date, Newcastle disease and avian influenza virus have not been reported in commercial poultry. Avian metapneumovirus was found in 7.2% (8/110) of the broiler samples. Antibodies to gyrovirus and avian leukosis virus have been detected. Commercial vaccines, such as attenuated, inactivated and vectored vaccines, are being used for prevention and control of viral poultry diseases in Turkey. This review summarises the available information on viral poultry diseases in Turkey. It highlights the need to strengthen surveillance and reporting for diseases and addresses the vaccination practices used in Turkish poultry industry. The future prospects of vaccination and need to empower diagnostic capacity in controlling viral poultry diseases are discussed. The information presented here is aimed at improving research, prevention, and control of poultry diseases for researchers, veterinarians, policy makers and other professions related to poultry industry.